PENGARUHI PROFITABILITAS, STRUKTUR MODAL, NILAI PERUSAHAAN DAN LIKUIDITAS TERHADAP NILAI PERUSAHAN (Studi Pada Perusahaan Asuransi di Bursa Efek Indonesia Tahun 2010-2012) - Putra, Rizky Akbar; Herawati, Juni (Jurnal Ilmiah Mahasiswa FEB, 2014)
The creation of firm value can provide a positive impact to  the owner of the company or  shareholders. The purpose of this research is to examine the influence of  provitability  which is proxied to  return on assets  (ROA), capital structure which is proxied to  debt to equity ratio (DER),  firm size and  liquidity which is proxied to current ratio (CR) to the firm value which is proxied to price-book value  (PBV).  The population in this study is a  insurance  company on the Indonesia Stock Exchange during the period 2010 to 2012. Samples were taken by all of company in this population as much as 10 company. Processing and testing data using Software Statistical Product And Service Solution versi 16. Tested in this study used  multiple regression  analysis.  From the results of  multiple regression analysis known that  profitability, capital structure,  firm size  and liquidity  simultaneously affect firm value. Profitability  has  positive  effect, significant  and is the dominant variabel  on firm value.  Liquidity  has  negative effect  and significant  on firm value. Whereas in capital structure and  firm size variabel has negative effect and non significant on firm value.   Keywords:  Profitability, Capital Structure, Firm Size, Liquidity, Firm Value